The Pemanfaatan Akuaponik Dutch Bucket System Kangkung Darat dan Ikan Lele pada Masyarakat Pesisir Desa Bongo, Kecamatan Batudaa Pantai, Provinsi Gorontalo - ulfira ashari; Syamsir Syamsir; Muh Iqbal Jafar Jafar (Institut Pertanian Bogor, 2022)
Coastal communities in general depend on the sea so that the fulfillment of food in the form of side dishes generally does not vary. Coastal communities have large enough yards for agricultural cultivation and freshwater fisheries, they are constrained by environmental factors (threats of drought and salinity). For this reason, problem solving efforts were carried out by designing and making an aquaponic system with the Dutch Bucket System (DBS) as well as training and education on horticultural cultivation techniques land kale (Ipomea reptana) and catfish (Clarias gariepinus) which were combined in the DBS model. The purpose of this service activity is to provide knowledge and understanding to partners about how to cultivate Aquaponics on horticultural plants (land spinach) and freshwater fish (catfish) through DBS technology. Partners are housewives who live in Bongo Village, Batudaa Pantai District, Gorontalo Province. The result of this service activity is additional knowledge and understanding of coastal communities regarding aquaponic cultivation techniques using the DBS. This activity is beneficial for the PKK group of women in fulfilling daily food diversity, reducing the monthly expenditure of vegetables and side dishes by 66.7% and providing education related to the use of yards on coastal land.